“Ngobrol Emak Tentang Anak” Konseling Daring Gratis Tentang Kesehatan Anak Pada Ibu di Wilayah Kabupaten Cilacap - Andin Sefrina, Ns., M.Kep., Sp.Kep.An. (JPS : Jurnal Pengabdian Serulingmas, 2022)
The ongoing COVID-19 pandemic is forcing us to minimize outdoor activities. Therefore, the situation becomes challenging when the mothers must nurse children with various health problems at home without access to a health facility. Based on a preliminary study, sometimes mothers do not have sufficient knowledge about children’s care, so they often develop anxiety if children’s development become unoptimized, especially because the children couldn’t learn at school and play outside. Those phenomena point out that there are issues experienced by the mothers related to children’s nursery at home. The proposer did community service in the form of Free Online Counseling with the title “Ngobrol Emak Tentang Anak” as one of the solutions to the problems. The aim of these programs is child’s growth and development optimization, children’s health safety during the COVID-19 pandemic, and adding mother’s knowledge and skills to children’s nurseries at home. The program is followed by 11 clients (the mothers) using WhatsApp chat media. Various client’s problems in this program include child’s nutrition, constipation, tantrum, sibling rivalry, and smartphone addiction. The conclusions from the results of this program are the client’s knowledge and problem-solving skills were enhanced to overcome various child’s health problems during the COVID-19 pandemic. Those things have a positive impact on a child’s health level and the child’s health optimization during the COVID-19 pandemic.